220k views
3 votes
6n(5n + 3) = 0
solve this equation by factoring

1 Answer

6 votes
n = 0, n= -3/5 OR n=0,-3/5

solution:

1- distribute:
6n(5n+3)=0
30n^2+18n=0

2- use the quadratic formula shown in the attached pic and substitute the numbers.

3- simplify:
n= -18 ± 18/60

4- separate the equations so you have one for the negative numbers and the other for the positive numbers:
a) n= -18+18/60
b) n=-18-18/60

5- solve:
a) n= 0
b) n= -3/5
6n(5n + 3) = 0 solve this equation by factoring-example-1
User Quentin Morrier
by
4.9k points